مفهوم التصوف وأنساقه المعرفية عند الشيخ عبد الحليم بن سماية - شروانة, رقية (جامعة الوادي university of eloued, 2022)
الملخّص: انبرى الشيخ عبد الحليم بن سماية إلى خوض معركة فكرية لتصحيح المفاهيم وإعادة الاعتبار للتصوف النقي بعد سنوات من التزييف التي قادها الاستشراق الفرنسي وأعوانه لخلق منظومة فكرية عميلة للاستعمار تسعى لزرع روح الاستسلام في نفسية الشعب الجزائري. لقد شكلت هذه التجربة خصوصية في حركة الإصلاح نظرا لحجم المسؤولية التي تحملها الشيخ عبد الحليم بن سماية في حياته ودفع قواه العقلية ثمنا لها، حيث فقد رشده وأخذ يهيم في شوارع مدينة الجزائر وخارجها في آخر حياته رحمه الله. وتقديرا للريادة والسبق في الأفكار التي نادى بها والتي كان لها تأثيرها في السياسة والاجتماع والتربية تقف هذه المقاربة لرصد معالم هذا التحول الفكري والثقافي في تاريخ النخبة الجزائرية في صراعها مع الاستعمار، وبيان الوعي الصوفي ومقاماته، وفهم دور الصوفي وأخلاقه وسلوكاته.Abstract : Sheikh Abdel Halim bin Samaya embarked on an intellectual struggle to correct concepts and restore pure Sufism after years of distortion led by French Orientalism and its some of its links in order to generate an intellectual colonialism puppet system that aimed to instill a submissive spirit in the psyche of the Algerian people. Such an enterprise constituted a specificity within the reform movement due to the amount of responsibility that Sheikh Abdel Halim bin Samaya bore in his life, responsibility that he paid his mental powers for, as he lost his senses and began wandering in the streets of Algiers by the end of his life. Recognizing the leadership and precedence of his ideas that had an influence on politics, sociology and education, the present paper intends to scrutinize the features of this intellectual and cultural shift in the history of the struggle of the Algerian elite against colonialism, to elucidate the Sufi awareness and its positions and to understand the role of the Sufi, his morals and behavior
The Concept Of Sufism And Its Cognitive Systems For Sheikh Abdul Halim Bin Samaya
مقال
Keywords: الإصلاح ؛التصوّف ؛التحول الفكري ؛الأنساق المعرفية.